2016
DOI: 10.14245/kjs.2016.13.2.53
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Herniated Disc at Cervicothoracic Junction Level Treated by Anterior Approach

Abstract: ObjectiveThe anterior approach for C7-T1 disc herniation may be challenging because of obstruction by the manubrium and the narrow operative field. This study aimed to investigate the clinical and neurological outcomes of anterior approach for C7-T1 disc herniation.MethodsWe retrospectively evaluated 13 patients who underwent the anterior approach for C7-T1 disc herniation by a single surgeon within a period of 11 years (2003-2014). The minimum follow-up duration was 6 months. We describe the clinical presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A standard Smith-Robinson anterior cervical approach is utilized. [24][25][26][27] Large anterior cervical osteophytes are usually the main cause of compression of the esophagus and other anterior structures. Studies on some controversial surgical protocols found that patients who had operative treatment using these protocols had good improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A standard Smith-Robinson anterior cervical approach is utilized. [24][25][26][27] Large anterior cervical osteophytes are usually the main cause of compression of the esophagus and other anterior structures. Studies on some controversial surgical protocols found that patients who had operative treatment using these protocols had good improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Added difficulties in our case came from the fact that the disc herniation needing repair involved the cervicothoracic junction (CTJ). Anterior approaches to the CTJ are challenging because of the close proximity to the sternal manubrium as well as the steep slope of the vertebral bodies of this particular region (C7/T1 level) [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cervical decompression and fusion (ACDF) is an effective treatment for many patients with pathology at C7-T1 [1] , [2] , [4] , [5] , [6] . There is little data regarding the results of cervical disc replacement (CDR) at the cervicothoracic junction.…”
Section: Introductionmentioning
confidence: 99%